Central retinal artery occlusion: a stroke of the eye - Chen, Celia; Singh, Gurfarmaan; Madike, Reema; Cugati, Sudha (Eye (London), 2024)
Central retinal artery occlusion (CRAO), like a stroke in the brain, is a critical eye condition that requiring urgent medical attention. Patients with CRAO present with acute loss of vision and the visual prognosis is poor with low chance of spontaneous visual recovery. Moreover, the risk of developing ischaemic heart disease and cerebral stroke is increased due to the presence of underlying atherosclerotic risk factors. Currently, there is no officially recommended treatment for CRAO. This review will describe the anatomy, pathophysiology, clinical features of CRAO, as well as exploring existing and potential future approaches for managing the condition.